Omega-3 fatty acid supplementation and cardiovascular disease - Donald B. Jump; Christopher M. Depner; Sasmita Tripathy (Journal of Lipid Research, 2012)
Epidemiological studies on Greenland Inuits in the 1970s and subsequent human studies have established an inverse relationship between the ingestion of omega-3 fatty acids [C20–22ω 3 polyunsaturated fatty acids (PUFA)], blood levels of C20–22ω 3 PUFA, and mortality associated with cardiovascular disease (CVD). C20–22ω 3 PUFA have pleiotropic effects on cell function and regulate multiple pathways controlling blood lipids, inflammatory factors, and cellular events in cardiomyocytes and vascular endothelial cells. The hypolipemic, anti-inflammatory, anti-arrhythmic properties of these fatty acids confer cardioprotection. Accordingly, national heart associations and government agencies have recommended increased consumption of fatty fish or ω 3 PUFA supplements to prevent CVD. In addition to fatty fish, sources of ω 3 PUFA are available from plants, algae, and yeast. A key question examined in this review is whether nonfish sources of ω 3 PUFA are as effective as fatty fish-derived C20–22ω 3 PUFA at managing risk factors linked to CVD. We focused on ω 3 PUFA metabolism and the capacity of ω 3 PUFA supplements to regulate key cellular events linked to CVD. The outcome of our analysis reveals that nonfish sources of ω 3 PUFA vary in their capacity to regulate blood levels of C20–22ω 3 PUFA and CVD risk factors.